Juridical Analysis of the Appointment of Acting Officials in the Simultaneous Regional Elections in 2024 and its Implications for the Principles of Democracy in Indonesia - Zalukhu, Alilin; Simamora, Janpatar; Siregar, Hisar (Indonesian Journal of Law and Justice, 2025)
This study analyzes juridically the appointment of Acting Regional Heads in regional head elections (Pilkada) held simultaneously in 2024 and its implications for the principles of democracy in Indonesia. In the context of simultaneous regional elections, the vacancy of the position of regional head caused by the term of office that ends before the implementation of the elections is filled by the Acting Regional Head based on the provisions of Article 201 paragraph (9), (10), and (11) of Law Number 10 of 2016 governing Regional Head Elections. Acting Heads are appointed from among officials with Middle high-leadership positions in the Governor, and Primary high-leadership in the Regent or Mayor. This research uses a normative juridical method with a doctrinal approach, namely analyzing relevant legislation, jurisprudence, and the views of legal experts. The analysis shows that the appointment of Acting Regional Head is a strategic policy needed to maintain the continuity of regional government. However, the appointment mechanism that is fully determined by the central government without community involvement has various implications for democratic principles, such as reduced public participation, reduced accountability of the process of filling positions, and the absence of direct accountability to the people. The implications of the results of the analysis and studies in this research can be input and consideration for policy makers to improve the legal framework governing the appointment of Acting heads, so as to strengthen democratic principles and maintain political and government stability at the provincial, district or city level.